Effective Communication and Startup Performance among Young Entrepreneurs (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Effective communication is increasingly recognized as a critical factor in the success and performance of startup ventures. However, many young entrepreneurs encounter communication-related challenges, including unclear information, weak feedback systems, and delays in communication, which can adversely affect employee coordination, decision-making, customer relations, and overall business performance. This study examined the influence of communication clarity, feedback mechanisms, and communication timeliness on startup performance among young entrepreneurs. A quantitative research approach was adopted, and data were analyzed using Structural Equation Modeling (SEM) to assess the relationships among the study variables. Model fitness was evaluated using multiple goodness-of-fit indices, including Chi-square statistics, Root Mean Square Error of Approximation (RMSEA), Standardized Root Mean Square Residual (SRMR), Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), and the Coefficient of Determination (CD). Three hypotheses were tested to determine the effects of clarity of information, feedback mechanisms, and communication timeliness on startup performance using path coefficients, standard errors, z-values, and p-values. The findings revealed that clarity of information (β = 0.2373, p < 0.05), feedback mechanisms (β = 0.3395, p < 0.01), and communication timeliness (β = 0.2808, p < 0.01) exert positive and statistically significant effects on startup performance. The results suggest that clear communication enhances employee understanding and operational effectiveness, effective feedback mechanisms support continuous improvement and goal alignment, while timely communication facilitates responsiveness and efficient decision-making. The study concludes that effective communication strategies are essential for improving startup performance among young entrepreneurs. It recommends that startup founders prioritize clear information sharing, establish structured feedback systems, and ensure timely communication to enhance business growth, operational efficiency, and long-term sustainability.